Geochronological and geochemical data for Late Palaeozoic–Mesozoic intrusive rocks in the Wenkutu area, northeastern China: New constraints on the tectonic evolution of the Great Xing'an Range. (14th March 2019) - Lu, Sheng; Wang, Ke‐Yong; Liu, Yang; Deng, Chang‐Zhou; Jing, Bo‐yu
Abstract : The occurrence of igneous rocks within the Wenkutu area, northeastern China, allows the Late Palaeozoic–Mesozoic geodynamic setting of the Great Xing'an Range to be investigated. Here, we present petrographic, geochemical, and geochronological data for intrusive rocks within the Wenkutu area. Zircon U–Pb geochronology reveals that magmatism occurred during the Early Carboniferous (ca. 334 Ma), Early Permian (ca. 296 Ma), Middle Jurassic (ca. 170 Ma), and Early Cretaceous (ca. 130 Ma). The Early Carboniferous intrusive rocks are intermediate–mafic, metaluminous, and medium‐K calc‐alkaline, have low SiO2 (49.57–55.00 wt.%) and high MgO (3.00–4.77 wt.%), Cr (average 60.64 ppm), and Ni (average 24.73 ppm) contents, and high Mg # (average 45.1) values. These features, together with their significant depletion in Nb, Ta, and Ti, and their enriched Sr–Nd isotopic compositions, suggest that these Early Carboniferous rocks were derived from the mantle and subsequently contaminated by crustal material. The Early Permian, Middle Jurassic, and Early Cretaceous intrusive rocks are intermediate–acidic, peraluminous, and high‐K calc‐alkaline, enriched in light rare‐earth elements, Rb, Th, U, K, P, and Hf, relatively depleted in heavy rare‐earth elements, Nb, Ta, and Ti, and have Eu/Eu* values of 0.05–0.86. These features indicate that the rocks were derived by the partial melting of lower crust. Our results, together with those of previous studies, suggest that the Late Palaeozoic intrusive rocks formed during collision between the Songnen and Xing'an massifs. The Early Permian intrusive rocks formed during the transition from an orogenic to a non‐orogenic environment. The Middle Jurassic intrusive rocks formed during the closure of the Mongol–Okhotsk Ocean (MOO) and were emplaced along the western part of the suture zone. The Early Cretaceous intrusive rocks formed during non‐orogenic extension and were related to the final closure of the MOO or to rollback of the Palaeo‐Pacific Plate.